Anti-cancer effects of disulfiram in head and neck squamous cell carcinoma via autophagic cell death - Park, Young Min; Go, Yoon Young; Shin, Sun Hwa; Cho, Jae-Gu; Woo, Jeong-Soo; Song, Jae-Jun (PLOS ONE, 2018)
Background Disulfiram (DSF), which is used to treat alcohol dependence, has been reported to have anti-cancer effects in various malignant tumors. In this study, we investigated the anti-cancer effects and mechanism of DSF in HNSCC. Methods Head and neck squamous carcinoma cell lines (FaDu and Hep2) were used to analyze the anti-cancer effects of DSF. The anti-cancer effects of DSF were confirmed in vivo using a xenograft tumor model. Results The anti-cancer effects of DSF in HNSCC were found to be copper (Cu) dependent. Specifically, DSF/Cu markedly inhibited HNSCC at a concentration of 1 μM. After DSF/Cu administration, production of reactive oxygen species (ROS) was remarkable starting at 0.5 μM, suggesting that the inhibitory effects of DSF/Cu on HNSCC are mediated through the formation of ROS. The levels of phospho-JNK, phospho-cJun and phospho-p38 were increased after DSF/Cu treatment while levels of phospho-Akt were decreased. These results suggested that the inhibitory effects of DSF/Cu on HNSCC cells involve ROS formation and down-regulation of Akt-signaling. Through these molecular mechanisms, DSF ultimately induce the inhibitory effects on HNSCC cell lines mainly through autophagic cell death, not apoptotic cell death. Lastly, we investigated the clinical relevance of DSF/Cu using a HNSCC xenograft animal model, which showed that tumor growth was remarkably decreased by DSF (50 mg/kg injection). Conclusion In treating patients with HNSCC, DSF may contribute to improved HNSCC patient’s survival. The characteristic anti-cancer effects of DSF on HNSCC may suggest new therapeutic potential for this medication in HNSCC patients.